Transgenerational Epigenetic Programming of the Embryonic Testis Transcriptome - Anway, Matthew D. (2007)
Embryonic exposure to the endocrine disruptor vinclozolin during gonadal sex determination appears to promote an epigenetic reprogramming of the male germ-line that is associated with transgenerational adult onset disease states. Transgenerational effects on the embryonic day 16 (E16) testis demonstrated reproducible changes in the testis transcriptome for multiple generations (F1-F3). The expression of 196 genes were found to be influenced, with the majority of gene expression being decreased or silenced. Dramatic changes in the gene expression of methyltransferases during gonadal sex determination were observed in the F1 and F2 vinclozolin generation (E16) embryonic testis, but the majority returned to control generation levels by the F3 generation. The most dramatic effects were on the germ-line associated Dnmt3A and Dnmt3L isoforms. Observations demonstrate that an embryonic exposure to vinclozolin appears to promote an epigenetic reprogramming of the male germ-line that correlates with transgenerational alterations in the testis transcriptome in subsequent generations.